Attitudes of Different Age Groups Toward People With Intellectual Disability During the COVID-19 Pandemic - Domagała-Zyśk, Ewa (Frontiers in Psychiatry, 2021)
Background: The COVID-19 pandemic has been particularly risky for people with disabilities and severe medical conditions, not only because the virus may be a direct threat to their physical health but also because of social exclusion and negating their needs and rights. Objective: This study aimed to assess the attitudes of people from different age groups toward people with intellectual disability (ID). Methods: The study included 223 people (19–85 years old) and was conducted in May 2020 – Januuary 2021. Data was collected using the Multidimensional Attitudes Scale Toward Persons With Disabilities and a self-designed Questionnaire regarding the attitudes toward people with ID during the pandemic. Data analysis was performed using SPSS 24 (ANOVA). Results: The results of the study showed that the general attitudes were only slightly supportive and differed among people of different age groups: the youngest and the oldest generation expressed the most positive attitudes while the adults (35-60 y.o.) expressed the most negative ones. Conclusions: As the pandemic is spreading rapidly with no definitive solution, awareness to create more positive attitudes toward people with ID and recognizing their needs is essential.